Description of Navicula vanseea sp. nov. (Naviculales, Naviculaceae), a new species of diatom from the highly alkaline Lake Van (Republic of Türkiye) with complete characterisation of its organellar genomes and multigene phylogeny - Elif Yılmaz; David G. Mann; Romain Gastineau; Rosa Trobajo; Cüneyt Nadir Solak; Ewa Górecka; Monique Turmel; Claude Lemieux; Nesil Ertorun; Andrzej Witkowski (PhytoKeys, 2024)
The current article describes Navicula vanseea sp. nov., a new species of diatom from Lake Van, a highly alkaline lake in Eastern Anatolia (Türkiye). The description is based on light and scanning electron microscopy performed on two monoclonal cultures. The complete nuclear rRNA clusters and plastid genomes have been sequenced for these two strains and the complete mitogenome for one of them. The plastome of both strains shows the probable loss of a functional ycf35 gene. They also exhibit two IB4 group I introns in their rrl, each encoding for a putative LAGLIDADG homing endonuclease, with the first L1917 IB4 intron reported amongst diatoms. The Maximum Likelihood phylogeny inferred from a concatenated alignment of 18S, rbcL and psbC distinguishes N. vanseea sp. nov. from the morphologically similar species Navicula cincta and Navicula microdigitoradiata.